2018
DOI: 10.1002/chem.201804770
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity Studies of Amido‐Substituted Germanium(I)/Tin(I) Dimers and Clusters

Abstract: Three amide ligands of varying steric bulk and electronic properties were utilized to prepare a series of amido‐germanium(II)/tin(II) halide compounds, (LEX)n, (L= ‐N{B(DipNCH)2}(SiMe3), TBoL; ‐N{B(DipNCH)2}(SiPh3), PhBoL; ‐N(Dip)(tBu), DBuL; Dip=C6H3iPr2‐2,6; E=Ge or Sn; X=Cl or Br; n=1 or 2). Reductions of these with a magnesium(I) dimer, {(MesNacnac)Mg}2 (MesNacnac=[(MesNCMe)2CH]−, Mes=mesityl), afforded singly bonded amido‐digermynes (TBoLGe−GeTBoL and PhBoLGe−GePhBoL), and an amido‐distannyne (PhBoLSn−SnP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 71 publications
0
48
0
Order By: Relevance
“…The reduction of the amido-tin(II) bromide precursor with the magnesium(I) dimer [( Mes NacNac) Mg] 2 ( Mes NacNac = [(MesNCMe) 2 CH] À ) gave rise to the Sn 6 (NtBuDip) 6 II-Sn3 (Scheme 22). [67] All SnÀ Sn distances (2.811-2.941 Å) in II-Sn1 and II-Sn2 are slightly longer than the sum of the single-bond covalent radii of two Sn atoms (2.80 Å). [68] The SnÀ Sn bonds in II-Sn1 are longer compared with those in II-Sn2, due to the bulky substituents (Table 6).…”
Section: Hexastannaprismanementioning
confidence: 97%
See 1 more Smart Citation
“…The reduction of the amido-tin(II) bromide precursor with the magnesium(I) dimer [( Mes NacNac) Mg] 2 ( Mes NacNac = [(MesNCMe) 2 CH] À ) gave rise to the Sn 6 (NtBuDip) 6 II-Sn3 (Scheme 22). [67] All SnÀ Sn distances (2.811-2.941 Å) in II-Sn1 and II-Sn2 are slightly longer than the sum of the single-bond covalent radii of two Sn atoms (2.80 Å). [68] The SnÀ Sn bonds in II-Sn1 are longer compared with those in II-Sn2, due to the bulky substituents (Table 6).…”
Section: Hexastannaprismanementioning
confidence: 97%
“…In 2019, Jones and coworkers reported the isolation of a twisted hexastannaprismane. The reduction of the amido‐tin(II) bromide precursor with the magnesium(I) dimer [( Mes NacNac)Mg] 2 ( Mes NacNac=[(MesNCMe) 2 CH] − ) gave rise to the Sn 6 (NtBuDip) 6 II‐Sn3 (Scheme ) …”
Section: Prismane IImentioning
confidence: 99%
“…In 2009, following an unusual account of stannylene binding to a strained alkyne,19 Power and co-workers documented the first reversible addition of ethylene to a distannyne complex 20. Subsequently, the reactions of alkenes with digallynes,21 digermynes,2224 silylenes,25,26 low-valent magnesium( i ) reagents,27 and a diazadiborinine have been reported 28. In all but the diazadiborinine system, the alkene scope is limited to ≤2 examples.…”
Section: Introductionmentioning
confidence: 99%
“…Tetrel bonds, described as "the tendency of heavier tetrel atoms to interact with anions or electron rich atoms" 70 belong to this family of σ-hole bonds, and have benefited from recent study, both theoretically and experimentally. [71][72][73][74][75][76][77][78][79] As a very recent example, calculations of the TH3 + (T = C, Si, Ge) complexes with H2 showed that H2 can serve as a tetrel bond acceptor through its σbond, and that the fundamental nature of the TH5 + depends on the identity of the T atom. It has also recently been reported that an S•••Sn contact plays a crucial role in activation of peroxisome proliferator-activated receptors (PPARs) by organotin molecules.…”
Section: Introductionmentioning
confidence: 99%